New alternative for human identification. Investigator IDplex Kit - QIAGEN® reproducibility: Latin American interlaboratory study - Builes, J. J.; Trejos, D.; Suárez, D.; Moreno, S.; Siza, L.; Acevedo, M.; Castillo, A.; Beltrán, L.; Ibarra, A.; Cicarelli, Regina Maria Barretto [UNESP]; Gaviria, A.; Zuluaga, L. (Elsevier, 2011)
In 2010 QIAGEN® launched to eight kits of different combinations of STRs, including the Investigator IDplex Kit. This kit allows amplification in one PCR 16 markers. The aim of this study was to evaluate the reproducibility of Investigator IDplex Kit among Latin America laboratories. In the framework of the 'III International Theoretical-Practice Course in Populations Genetic and Biologicals Filiations' in Medellín-Colombia, all participants were invited to evaluate the reproducibility of this kit, they were provided of the necessary materials for the study. The results reported by participating were tabulated for the study the reproducibility. Results and comments were received on the agreed date of 12 of the 22 laboratories registered, one participant submits comments only. Some laboratories reported greater sensitivity Investigator IDplex Kit compared with other kits containing similar markers, also highlight the easy adaptability to existing conditions in laboratories, without involving major changes to its implementation. This paper shows the high reproducibility of Investigator IDplex Kit, a new tool offered by QIAGEN® for all laboratories that perform human identification testing and biological relationship testing using DNA markers. © 2011 Elsevier B.V.
Keywords: Genetic markers; Human identification; Investigator IDplex; Reproducibility; STR; DNA marker; capillary electrophoresis; controlled study; DNA extraction; gene amplification; genetic identification; human; identification key; laboratory; priority journal; reproducibility; sensitivity analysis; short tandem repeat; South and Central America